The use of massive open online courses in teaching the fundamentals of programming to software engineers - Tetiana A. Vakaliuk; Oleksii V. Chyzhmotria; Olena H. Chyzhmotria; Svitlana O. Didkivska; Valerii V. Kontsedailo (Academy of Cognitive and Natural Sciences, 2023)
The article describes the possibilities of using massive open online courses (MOOC) in teaching the discipline "Fundamentals of Programming" to students majoring in software engineering. The content of studying the discipline "Fundamentals of Programming" and the number of hours allotted for its study in institutions of higher education in Ukraine is analyzed. When studying the discipline "Fundamentals of Programming" at the Zhytomyr Polytechnic State University, the study of the corresponding course on the platform of massive open online courses Sololearn is submitted for independent work. A description of the possibilities of using this MOOC in teaching the discipline "Fundamentals of Programming" to future specialists in software engineering is presented. In addition, using a pedagogical experiment, the effectiveness of using the Sololearn in teaching the discipline "Fundamentals of Programming" to future software engineering specialists was tested. The results of the pedagogical experiment showed the effectiveness of using the MOOC Sololearn in teaching the "Fundamentals of Programming" to future software engineering specialists.